Synthesis and characterization of multiarm (Benzoin-PS)m-polyDVB star polymer as a polymeric photoinitiator for polymerization of acrylates and methacrylates - Esen, Duygu Sevinc; Yigit, Nese Cakir; Tunca, Umit; Hizal, Gurkan; Arsu, Nergis (WILEY, 2021)
In this study, a new benzoin-based multi-arm star polymer was synthesized by using ATRP, and characterization was achieved by spectrophotometric and chromatographic methods. Obtained multiarm (Benzoin-PS)(m)-polyDVB star polymer was employed as a polymeric photoinitiator for polymerization of methacrylates and acrylates. Photophysical properties of this initiator were determined by fluorescence and phosphorescence measurements, the phosphorescence lifetime was calculated as 29 ms hence the lowest triplet state nature was n-pi* character, and laser flash photolysis technique was additionally used to get more information about triplet state and triplet lifetime which was calculated as 1.34 ms. Photokinetics of difunctional acrylate such as HDDA was studied with a multi-arm (Benzoin-PS)(m)-polyDVB star polymeric initiator using Photo-DSC.
Keywords: benzoin; free radical polymerization; polymeric photoinitiator; star polymer; ONE-COMPONENT; CLICK CHEMISTRY; MAIN-CHAIN; THIOXANTHONE; BENZOPHENONE; MACROPHOTOINITIATORS; BLOCK; Polymer Science